Magnetic properties of bifunctional nitronyl-nitroxide radials with crystal lattice modulated by halogen bonding; High-Spin Molecules and Molecular Magnets (MolMag-2023) - Shurikov M. K. Matvey Konstantinovich (2023, 2023)
Title screen